Insights into the smooth‐to‐rough transitioning in Mycobacterium bolletii unravels a functional Tyr residue conserved in all mycobacterial MmpL family members. Issue 5 (18th December 2015) - Bernut, Audrey; Viljoen, Albertus; Dupont, Christian; Sapriel, Guillaume; Blaise, Mickaël; Bouchier, Christiane; Brosch, Roland; de Chastellier, Chantal; Herrmann, Jean‐Louis; Kremer, Laurent
Summary: In mycobacteria, MmpL proteins represent key components that participate in the biosynthesis of the complex cell envelope. Whole genome analysis of a spontaneous rough morphotype variant of M ycobacterium abscessus subsp. bolletii identified a conserved tyrosine that is crucial for the function of MmpL family proteins. Isogenic smooth (S) and rough (R) variants differed by a single mutation linked to a Y842H substitution in MmpL4a. This mutation caused a deficiency in glycopeptidolipid production/transport in the R variant and a gain in the capacity to produce cords in vitro . In zebrafish, increased virulence of the M . bolletii  R variant over the parental S strain was found, involving massive production of serpentine cords, abscess formation and rapid larval death. Importantly, this finding allowed us to demonstrate an essential role of Tyr842 in several different MmpL proteins, including Mycobacterium tuberculosis  MmpL3 . Structural homology models of MmpL4a and MmpL3 identified two additional critical residues located in the transmembrane regions TM10 and TM4 that are facing each other. We propose that these central residues are part of the proton‐motive force that supplies the energy for substrate transport. Hence, we provide important insights into mechanistic/structural aspects of MmpL proteins as lipid transporters and virulence determinants in mycobacteria. Abstract : MmpL4a is a membrane protein participating in the transport of glycopeptidolipids (GPL) in the Mycobacterium abscessus complex. Herein, we demonstrate the crucial role of Tyr842 in the activity of MmpL4a. This residue, proposed to be involved in the proton motive force driving MmpL activity, is conserved in all MmpL members. Using structural modeling and site‐directed mutagenesis, we provide important insights into mechanistic aspects of this family of transporters.